PENGARUH DIMENSI EKUITAS MEREK TERHADAP NIAT MEMBELI - Hendro Widjanarko (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
The objective of this study is to examine; (1) the simultaneous effects of brand awareness, advertising awareness, brand association and perceived quality on the intent to buy; (2) the partial effect of brand awareness, advertising awareness, brand association and perceived quality on the intent to buy; (3) is brand association a dominant variable that effect on the intent to buy. Survey was conducted to collect data from partisipants. The research used multiple linier regression to analyze data.The results show that simultaneously, brand awareness, advertising awareness, brand association and perceived quality have a significant effect on the intent to buy. The results also indicate that partially, brand association has a significat effect on the intent to buy. Nevertheless, brand awareness, advertising awareness and perceived quality have not significant effect on the intent to buy.